The fiancée [large type] : a novel - White, Kate, 1950- (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
Summer<U+2019>s looking forward to a break from hustling for acting work in Manhattan when she, her husband Gabe, and Gabe<U+2019>s nine-year-old son arrive at the annual family get-together at her in-laws<U+2019> sprawling estate. On the agenda are leisurely gourmet meals, tennis matches, and plenty of relaxation by the pool. But this year, Gabe<U+2019>s brother Nick has invited his new flame Hannah, whom Summer immediately recognizes from a few years before. Oddly, her brother-in-law<U+2019>s girlfriend claims not to know her. Yet she charms the other family members, and after Nick announces that he<U+2019>s proposed to Hannah, Summer doesn<U+2019>t have much choice but to grin and bear it. Then the reunion is rocked by tragedy when a family member is found dead. Though the doctors attribute the loss to natural causes, a grieving Summer fears that the too-good-to-be-true Hannah is involved, even as Gabe dismisses her suspicions. How far will Summer go to expose the truth? As she investigates just what Nick<U+2019>s fiancée might have done to keep her perfect image intact, she begins to fear that the first death might only be the beginning .